Efficient Air-Based Thermal Management for Electric Two-Wheeler Batteries: A CFD Approach - Munzir Qadri; Wahid Hasim; Erwinda Fenty Anggraini; Riki Effendi; Fadwah Maghfurah (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Effective thermal management is critical for ensuring the performance, safety, and longevity of lithium-ion batteries (LIBs) in electric two-wheeled vehicles. This study develops a cost-efficient, air-based Battery Thermal Management System (BTMS) for a 460 Wh battery pack. As LIBs can convert up to 20% of input energy into heat due to internal resistance and electrochemical reactions, inadequate heat dissipation may lead to thermal runaway, potentially causing fire or explosion. Computational Fluid Dynamics (CFD) simulations were employed to explore and optimize various air-cooling configurations. The most effective design—identified through simulation—was experimentally validated using an electronic battery tester under high-current loads. Results indicate that an optimized push-pull air-cooling configuration significantly reduces peak battery temperatures and maintains them within safe operational limits, thereby enhancing battery reliability and extending its lifecycle. This work contributes to the advancement of practical and affordable thermal solutions for sustainable electric mobility, particularly in the low-power vehicle segment.